(untitled) (Journal of Management and Social Sciences, 2022)
Teleworking has become a new work practice in many organizations accentuated by the recent COVID-19 pandemic. Contending findings in the literature on the relationship between teleworking and employee performance in various industries motivated this new study. The paper seeks to examine the effect of teleworking on team performance in the public sector in Nigeria. The study is focused on selected government agencies in Abuja and Kaduna State, Nigeria. 384 questionnaires are administered on the senior staff of these agencies, and quantitative method is adopted to measure the effect of remote work and team communication on the performance of the team members. SPSS software is used to analyse the data collected, and descriptive statistics and multiple regression analysis are undertaken to determine the effect of teleworking on team performance. The statistical tests conducted reveal a significant relationship between remote work and team performance. Findings also show there is significant relationship between team communication and team performance in the Nigerian public sector. Recommendations are proposed that governments should create a policy on remote work for workers in the public sector, and increased investments should be made in ICT infrastructure in order to increase the motivations and efficiencies of workers. Keywords Teleworking, team performance, Nigeria, organization, remote work